Silicon nano-kirigami with controlled plastic, elastic and hysteretic deformations - Qinghua Liang; Zhiguang Liu; Yu Han; Shang Chen; Haozhe Sun; Yingying Chen; Yongyue Zhang; Meihua Niu; Chongrui Li; Yang Wang; Ke Jin; Yongtian Wang; et al. (Nature Communications)
Abstract Nano-kirigami, inspired by the art of paper cutting and folding, offers a promising approach to three-dimensional (3D) nanomanufacturing by simply transforming two-dimensional (2D) precursors into complex 3D architectures. Here we report a profound study on three types of deformation behaviors of silicon-based nano-kirigami structures, including plastic, elastic, and hysteretic deformations. Three-stage bidirectional plastic deformations with double reversals, driven by ion-induced stress gradients, are observed and well explained by developing a torque model, revealing the critical stress competition caused by ion implantation and vacancy distribution during gallium ion irradiations. Fast-recovering elastic deformations are generated under mechanical or electrical stimuli, which can support mechanical response at a 10 nano-Newton level and optical modulation with high repeatability. Extraordinary hysteretic deformations with fast-changing and long-tail recovery periods are observed, which are uncovered by a capacitor-like charge accumulation mechanism. The controllable elastic and hysteretic deformation modes are further employed to demonstrate the applications in dynamic optical information encryption. This work reports a useful methodology to design, fabricate, and manipulate silicon-based nano-kirigami structures with great potential for applications in micro-electromechanical systems (MEMS), nano-opto-electromechanical systems (NOEMS), micro-/nano-machinery and other advanced nanotechnologies.